Periodontitis Provokes Retinal Neurodegenerative Effects of Metabolic Syndrome: A Cross-Sectional Study - Hatice Arslan; Nur Yorgancilar; Oguz Kose; Mehmet Gokhan Aslan; Ahmet Altin; Sevda Kurt Bayrakdar; Hatice Yemenoglu; Huseyin Findik; Adnan Yilmaz (Dentistry Journal)
Background: This cross-sectional study aims to investigate the retino-choroidal degenerative effects of periodontitis, metabolic syndrome (Mets), and the combination of these diseases using optical coherence tomography (OCT) measurements. Methods: Ninety-two patients selected according to inclusion criteria were divided into four groups: systemically and periodontally healthy (control), systemically healthy periodontitis (PD), periodontally healthy metabolic syndrome (MetS), and periodontitis and metabolic syndrome combined (PD-MetS). The systemic inflammatory–oxidative effects of periodontitis and MetS were biochemically evaluated using the serum TNF-α level, IL-1β/IL-10 ratio, and oxidative stress index (OSI: TOS/TAS). Retinal (AMT, pRNFLT, and GCL + T) and choroidal (SFCT) morphometric measurements and vascular evaluations (foveal capillary density) were performed via OCT Angio with swept-source technology. Results: Both periodontitis and Mets cause systemic inflammatory stress characterized by significant increases in the IL-1β/IL-10 ratio and OSI (p < 0.05). Compared to the control group, the AMT was significantly thinner in the MetS group, the pRNFLT was significantly thinner in the PD-MetS group, and the SFCT was significantly thinner in both groups (p < 0.05). The GCL+ was slightly thicker in the Mets groups. (p > 0.05) Foveal capillary density did not differ significantly among the groups. (p > 0.05). Conclusions: Periodontitis-related inflammatory stress alone causes changes in retinal and subfoveal choroidal thicknesses that are not statistically significant. On the other hand, when combined with Mets, it may significantly provoke the retinal neurodegenerative effects of this disease.